Pengaruh Pakan dari Famili Brassicaceae terhadap Siklus Hidup Spodoptera litura - Tri Azizah, Faisna; Widjajati, Wiludjeng; Megasari, Dita (BIOEDUSCIENCE, 2025)
Background: S. litura has a wide host range, so it has the potential to become a pest on various types of plants, including food crops, horticulture, and plantations. The quality and quantity of food determine the nutritional needs of insects, so they greatly influence their growth and length of development. This research aimed to determine the life cycle length, body length, pupa weight, fecundity, and prevalence of S. litura in several natural foods from the same plant family. Method: This study used non-factorial RAL with five treatment levels and was repeated 7 times. Results: The feed that survived to the imago stage was cauliflower, green and white mustard greens, and produced eggs. The fastest life cycle for cauliflower feed is 24 days, green mustard greens are 30 days, and white mustard greens are 25 days. The eggs that successfully hatched were in the Sh and Sp treatments, with Sh with 12% egg fertility and Sp 74%. Conclusion: The different types of 5 different feeds show different growth and development results for S. litura depending on the amount and content of the feed itself.